The Effects of Cam Femoroacetabular Impingement on Mechanical Hip Joint Loading - Ng, Kwan-Ching Geoffrey (Université d'Ottawa / University of Ottawa, 2017)
A major contributing factor to the onset of early hip osteoarthritis is attributed to an enlarged, aspherical femoral head deformity, characterized as cam-type femoroacetabular impingement (FAI). The presence of the cam deformity alone does not explain differences in pathomechanisms and it has been theorized that adverse loading to the subchondral bone may play a predominant mechanical role in early joint degeneration. This doctoral thesis examined the adverse hip joint loading due to cam FAI and characterize mechanical stimuli associated with symptoms. Specifically, this research: 1) examined anatomical and functional characteristics associated with the cam morphology; 2) developed subject-specific finite element hip joint models to examine hip joint stresses, incorporating subject-specific geometries, materials properties, and joint loading; and 3) implemented loading parameters during level walking and squatting to examine hip joint stresses. First, a classification study was conducted to recruit three participant groups: 1) symptomatic (where participants had the cam deformity and pain); 2) asymptomatic (where participants had the cam deformity, but no pain); and 3) control (where participants did not have the cam deformity or clinical signs). Each participant's CT data were evaluated for multiple anatomical hip joint parameters and then re-classified into their respective subgroups, using a discriminant function analysis, based on the most significant parameters. In addition to the cam deformity, symptomatic individuals had a lower femoral neck-shaft angle and reduced pelvic range of motion. Second, using the classified participants, hip joint loading was determined for the various severities of cam FAI, with respect to alterations in hip contact forces and anatomical considerations. Hip joint assemblies were segmented and reconstructed from subject-specific CT and MRI data, where bone densities were quantified from CT data. A parametric study was conducted to understand how varying material properties and loading conditions affected the sensitivity of the predictive models, examining the most appropriate modelling parameters to capture relative measurements. Third, in conjunction with the first two studies, hip contact forces for level walking and squatting tasks were applied to corresponding subject-specific models and simulated. As a cross-sectional analysis, the stress magnitudes and regions described the joint loading in vivo for each subject group and ascertained the risk of remodeling. For each subgroup (symptomatic, asymptomatic, control), the participants with the largest and smallest femoral neck-shaft angles were selected and compared. The symptomatic model with the lowest femoral neck-shaft angle demonstrated the highest stress on the cartilage, during walking and squatting, and on the subchondral bone, during squatting. The asymptomatic models showed cartilage stresses similar to the control group, but experienced high-risk subchondral bone stresses, similar to the symptomatic group. For both symptomatic and asymptomatic groups, the acetabular subchondral bone stresses coincided with known areas of bone adaptation and proteoglycan depletion. The outcome of this research program supported that cartilage degradation might not be due to direct contact shear stresses, but perhaps rather attributed to the indirect effects of a stiffer subchondral bone plate. Individuals with a large cam deformity and decreased femoral neck-shaft angles are likely to experience severe subchondral bone stresses during higher amplitudes of hip motion. This provides clinicians with indications of how the pathology exacerbates and where initial cartilage delamination will likely occur, allowing them to perform the correct assessments and proceed with the correct form of care. From a patient's perspective, an early and accurate diagnosis could inhibit cartilage degradation and the progression of osteoarthritis.
Keywords: femoroacetabular; impingement; hip; cam; symptomatic; anatomical; finite element; stress